STRATEGI PEMASARAN PADA PLATFORM E-COMMERCE SHOPEE - Ismalia, Silfa; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
The purpose of this study is to see how the Shopee e-commerce platform uses marketing strategies to increase its competitiveness and market share in Indonesia. Shopee, one of the largest e-commerce platforms in Southeast Asia, has managed to attract customers with a variety of innovative marketing strategies. Literature study methods and secondary data analysis from journal articles and related official publications are used in qualitative descriptive research. The results of the study show that Shopee uses several main strategies: aggressive in promotions, consumer loyalty programs through Shopee coins, successful digital marketing campaigns such as flash sales, discounts and free shipping, and Shopee affiliates. These strategies have proven successful in attracting new customers and retaining old ones. In conclusion, Shopee can increase sales and increase brand awareness by utilizing digital marketing strategies correctly. It is hoped that this research will be beneficial to other e-commerce companies as they create a successful marketing strategy.